People who are transgender: mental health concerns. Issue 1 (7th November 2014) - McCann, E.
<x xml:space="preserve">Abstract</x> Accessible summary The aim of the study was to elicit the views and opinions of transgender people in relation to mental health concerns. Four people who identified as transgender participated in semi‐structured interviews. The main results showed that challenges existed for people around mental health issues. Mental health nurses can play a key role in the provision of psychosocial supports to transgender people and their families. Abstract Government policy makers are becoming increasingly interested in the views and experiences of people who utilize mental health services to inform rights‐based and socially inclusive health and social care initiatives. However, very little information exists in the available literature about transgender people in this regard. The current research was part of a larger mixed methods study that used surveys and in‐depth semi‐structured interviews. This paper reports on the findings from the interview data that relate to the unique mental health experiences of the people whom identified as transgender (n = 4). The data were subject to thematic analysis, and the main themes that emerged included service experiences, treatment issues, other supports, and hopes and aspirations. Participants identified challenges and opportunities for enhancing mental health service provision for transgender people and their families. Some of the highlighted concerns related to practitioner attributes and relevant psychosocial supports. Mental health nurses are well placed to use their knowledge and therapeutic skills to support people who identify as transgender and significant people in their lives.